Urbanisation dampens the latitude‐diversity cline in ants. Issue 6 (22nd July 2022) - Perez, Abe; Chick, Lacy; Menke, Sean; Lessard, Jean‐Philippe; Sanders, Nathan; Del Toro, Israel; Meldgaard, Niklas Sundebo; Diamond, Sarah
Abstract: The increase in species diversity from temperate to tropical regions is one of the most widespread patterns in biogeography. As humans continue to drastically modify natural habitats, land‐use changes such as the development of cities could potentially alter typical latitudinal diversity gradients. Cities could depress or enhance biodiversity through filtering, localised extirpations, or increasing niche availability, respectively. To address these possibilities and the consequences for the latitudinal diversity gradient, we constructed a global dataset of urban species diversity (richness) and community composition across 60° of absolute latitude and from 63 cities. We focused our study on ants, for which comparable urban and non‐urban diversity data are broadly available. We found that urbanisation significantly dampened the latitude‐diversity cline. The effects of urbanisation varied with latitude: at lower latitudes, cities were relatively species poor and harboured distinct ant communities relative to nearby non‐urban communities. In higher latitude cities, both species richness and community composition were more similar to the surrounding non‐urban ant communities. Our analyses suggest that the strongest impacts of urbanisation on ant diversity may be in the tropics, where biological diversity is already expected to experience the greatest risk of extinction in the face of climate change. Abstract : We constructed a global dataset of urban ant species diversity (richness) and community composition. We found that urbanisation significantly dampened the latitude‐diversity cline, with varying impacts across latitude. Lower latitude cities were species poor with distinct ant communities relative to nearby non‐urban communities. Urban and non‐urban species richness and community composition were more similar at higher latitudes. The strongest impacts of urbanisation on ant diversity may be in the tropics, where biological diversity is expected to experience the greatest risk of extinction due to climate change.